A novel rat tail disc degeneration model induced by static bending and compression. Issue 3 (26th August 2021) - Ji, Yichao; Zhu, Pengfei; Zhang, Linlin; Yang, Huilin
Abstract: Background: A new rat tail intervertebral disc degeneration model was established to observe the morphologic and biologic changes of static bending and compression applied to the discs. Methods: In total, 20 Sprague‐Dawley rats with similar weight were randomly divided into 4 groups. Group 1 served as a control group for a baseline assessment of normal discs. Group 2 underwent a sham surgery, using an external device to bend the vertebrae of coccygeal 8‐10. Groups 3 and 4 were the loaded groups, and external devices were instrumented to bend the spine with a compression level of 1.8 N and 4.5 N, respectively. Magnetic resonance imaging (MRI), histological, and quantitative real‐time PCR (qRT‐PCR) analysis were performed on all animals on day 14 of the experiment. Results: Magnetic resonance imaging and histological results showed that the changes of intervertebral disc degeneration increased with the size of compression load. Some architecture disorganizations in nucleus pulposus and annulus fibrosus were found on both of the convex and concave side in the groups of 1.8 N and 4.5 N. An upregulation of MM‐3, MM‐13, and collagen 1‐α1 mRNA expression and a downregulation of collagen 2‐α1 and aggrecan mRNA expression were observed in the sham and loading groups. Significant changes were found between the loading groups, whereas the sham group showed similar results to the control group. Conclusions: Static bending and compression could induce progressive disc degeneration, which could be used for biologic study on disc degeneration promoted by static complex loading.